Work and the city. - Duffy, Frank, ....- (London : Black Dog, 2008)
Frank Duffy, one of the leading thinkers on the future of the workplace, takes a hard look at the damage office development has done to the fabric and life of our cities. He analyses the theoretical approaches and development mechanisms that have led to sterilisation by commerce becoming the norm across the world. In Work and the City Duffy suggests ways to break out of this cycle and to develop offices in urban areas that bring benefits to both cities and the office users themselves.